Laughing off cyber spoofing: the role of self-deprecating humor in enhancing celebrities’ interpersonal likeability - Yi Cao; Hao Li; Tonglin Jiang; Junhua Dang; Yubo Hou (BMC Psychology)
Abstract Background Given the increasing prevalence of cyber spoofing and satire targeting public figures, understanding the psychological and social effects of self-deprecating humor can provide valuable insights into its effectiveness as a coping strategy. Methods Studies 1a (N = 183) and 1b (N = 198) manipulated self-deprecating humor and examined its effect on interpersonal liking using within-participant and between-participant designs, respectively. Study 2 (N = 205) explored the moderating role of social distance and Study 3 (N = 274) investigated the mediating role of perceived forgiveness in the distant condition. Results The results showed that using self-deprecating humor as a coping strategy increased the celebrity’s interpersonal likeability (Study 1). Moreover, self-deprecating humor was more effective in the distant condition than in the close condition (Study 2) and may enhance interpersonal liking through perceived forgiveness (Study 3). Conclusions These findings suggest that self-deprecating humor can serve as an effective strategy for celebrities to navigate cyber spoofing, particularly when addressing a distant audience. The study highlights the role of social distance and perceived forgiveness in shaping audience responses, offering practical implications for celebrity image management on social media.